Radioembolization of hepatocellular carcinoma activates liver regeneration, induces inflammation and endothelial stress and activates coagulation. (3rd June 2014) - Fernandez‐Ros, Nerea; Iñarrairaegui, Mercedes; Paramo, Jose A.; Berasain, Carmen; Avila, Matias A.; Chopitea, Ana; Varo, Nerea; Sarobe, Pablo; Bilbao, Jose I.; Dominguez, Ines; D'Avola, Delia; Herrero, J. Ignacio; et al.
Abstract Background & Aims Radioembolization may rarely induce liver disease resulting in a syndrome that is similar to veno‐occlusive disease complicating bone marrow transplantation where inflammation, endothelial cell activation and thrombosis are likely involved. We hypothesized that similar mechanisms could be implicated in radioembolization‐induced liver disease (REILD). Moreover, lobar radioembolization may induce hypertrophy of the non‐treated hemiliver most probably by inducing liver regeneration. Methods In patients with hepatocellular carcinoma, we prospectively studied serum levels of markers of liver regeneration, oxidative stress, pro‐inflammatory pathways, endothelial activation and coagulation parameters over 2 months after radioembolization. Results Although REILD did not occur among 14 treated patients, a decrease in effective liver blood flow was observed. Radioembolization was followed by a persistent increase in pro‐inflammatory (interleukin 6 and 8) and oxidative stress (malondyaldehide) markers, an induction of endothelial injury markers (vW factor and PAI‐1) and an activation of the coagulation cascade (factor VIII, PAI‐1, D‐Dimer) as well as a significant increase in factors related to liver regeneration (FGF‐19 and HGF). Conclusion Radioembolization activates liver regeneration, produces oxidative stress, activates inflammatory cytokines and induces endothelial injury with partial activation of the coagulation cascade. These findings may have implications in the pathogenesis, prevention and therapy of REILD and in the development of new therapies to enhance hypertrophy with a surgical perspective.